Comparison of LN2 and LCO2 based on machining performance indicators for drilling Inconel 718. (September 2022) - Shah, Prassan; Khanna, Navneet; Arora, Amit; Srivastava, Nishkarsh
Abstract: In the present scenario, global concern about the preservation of environment creates a necessity to mature more ecological manufacturing processes. In this context, cryogenic coolants i.e., liquid nitrogen (LN2 ) and liquid carbon dioxide (LCO2 ) are proved to be the prominent alternatives to conventional carbon-based flood coolant pollutants. However, the comparison of these cryogenic coolants based on machining performance is still lacking to cut the materials having low machinability like Inconel 718 at various cutting speeds ( v c ). In this context, thrust force, tool wear, and hole quality indicators using field emission scanning electron microscopy (FE-SEM) and Energy Dispersive X-ray Spectroscopy (EDS) analysis, microhardness, chip morphology for drilling Inconel 718 utilizing cryogenic fluids i.e., LCO2 and LN2 are extensively explored. Holes are drilled at three values of v c for both cooling conditions. By analyzing the mean of thrust force, 14 %, 9 %, and 31 % reduced values of it have been observed for LCO2 as compared to LN2 when the same quantity of holes are considered for v c as 10, 15, and 20 m/min correspondingly. Both cryogenic coolants reveal abrasion and chipping wear mechanisms on tools as significant at all v c . However, a higher worn region on the rake and flank face of drills was found for LN2 . A superior machining performance was observed for LCO2 in comparison with LN2 at all v c . The superiority of LCO2 over LN2 makes it suitable for high-value machining industries.